AB0055 Monocytes Are the Major Target Cells to Produce Cytokines When Stimulated by Microcrystals. (10th June 2014) - Scanu, A.; Oliviero, F.; Luisetto, R.; Fiocco, U.; Dayer, J.-M.; Punzi, L.
Abstract : Background: Crystal deposition in joints leads to leukocyte recruitment and a massive release of various inflammatory mediators, in particular cytokines and chemokines. These events are well reproduced by in vitro models in which the inflammatory response has been studied in different cell type. However, it has not yet determined the exact contribution of various articular cell populations when activated by different types of crystals. Objectives: To evaluate the in vitro response of different types of human cells, respectively polymorphonuclear cells (PMN), monocytes (M) and lymphocytes (L) for the production of cytokines in the presence of monosodium urate (MSU), calcium pyrophosphate (CPP) and basic calcium phosphate (BCP) crystals. Methods: MSU, CPP and BCP crystals were prepared according to Denko's, Cheng's and McCarthy's method respectively, and sterilized by heating at 180°C for 2 h before each experiment. PMN, M and L were isolated from peripheral blood of 4 healthy volunteers by density gradient centrifugation and differential adhesion. Cells were stimulated, in presence of polymyxin B, with increasing concentrations of crystals (0.01, 0.05, 0.1, 0.5, 1 mg/ml) for increasing time periods (0, 1, 2, 3, 9, 18, 24 h). Culture supernatants were tested by ELISA for the production of IL-1β, IL-8, IL-6, CCL2 and IL-1Ra. Results: Exposure of PMN to different crystals induced a low IL-8 production, but no detectable level of other cytokines evaluated. IL-8 levels peaked at 18 h after treatment with 0.5 mg/ml MSU (215.62±17.89 pg/ml), 0.01 mg/ml CPP (175.21±15.97 pg/ml) and 1 mg/ml BCP (105.75±6.31 pg/ml) crystals. In contrast, stimulation of M by MSU, CPP and BCP crystals resulted in a significant increase in the release of all cytokines assessed. The highest levels of IL-1β, IL-8 and IL-6 were observed with MSU at 0.5 mg/ml (201.09±6.10; 3190.00±74.81; 52.82±8.48 pg/ml respectively), CPP at 0.05 mg/ml (169.89±4.02; 1232.7±63.07; 36.94±9.47 pg/ml) and BCP at 1 mg/ml (146.01±6.36; 4133.2±56, 57; 49.5±2.69 pg/ml) after 18 h of treatment and then decreased after 24 h, whereas those of CCL2 reached a maximum at 3h (MSU: 153.96±11.35; CPP: 99.6±6.85; BCP: 59.42±4.13 pg/ml) and diminished at 9 h. IL-1Ra release induced by MSU, CPP and BCP crystals continued to increase until 24 h (100.03±14.66; 80.44±3.98; 70.85±2.13 pg/ml). MSU crystal-induced production of IL-1β and IL-1Ra was greater than that induced by other crystals. Stimulation of M by different crystals caused high secretion of IL-8 at all concentrations used. The production of IL-6 and CCL2 was similar in supernatants of M treated with the three types of crystals. Exposure of L to different crystals did not induce cytokine release. Conclusions: This study demonstrates that the three types of leukocytes from the same donor behave differently after stimulation with the crystals. IL-8, the only detectable cytokine in stimulated PMN, is induced by all types of crystals. In contrast, as compared to PMN, M produce many cytokines when stimulated with all types of crystals and represent the major target cells in this type of inflammation. No detectable levels of cytokines are found in crystal-stimulated L. Crystals induce a rapid increase of pro-inflammatory cytokines, whereas longer periods could be required to release high levels of anti-inflammatory cytokines such as IL-1Ra. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4996